Seismic performance of steel special moment resisting frames with different span arrangements - Ozhendekci, Devrim; Ozhendekci, Nuri (ELSEVIER SCI LTD, 2012)
Span arrangement is a crucial parameter from the designer's perspective, since it directly affects the seismic performance and economy of design. However, previous studies have not paid sufficient attention to the evaluation of its effects. Thus three 10-story steel special moment resisting frames with different span arrangements are designed according to the procedures of Turkish seismic design codes which are very similar to allowable stress design and capacity design procedures provided in AISC Manual and Seismic Provisions for Structural Steel Buildings. With the chosen geometric properties, design earthquake load and seismic effective mass is kept constant for model frames which is thought to be convenient for comparison purposes. The buildings are analyzed with OPENSEES under 15 simulated ground motion records and seismic performance assessment is carried out for collapse prevention performance level according to nonlinear dynamic procedure of FEMA 356. SIMQKE program is utilized to simulate ground motions, mean spectrum of whose matches to 1.5 times the design spectrum resulting in an earthquake hazard level of 2% probability of exceedance in 50 years. The entire model frames are found to satisfy the acceptance criteria for collapse prevention performance level. Based on the results of the structural systems used in this study, model frame with span length to story height ratio of approximately 2 seems to maintain both performance and economy, while the ratio higher than 2.5 can result in relatively high deflections and high element plastic rotations in lower stories under infrequent earthquake loads which render the frame seismically vulnerable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Steel special moment resisting frames; Seismic performance assessment; Collapse performance; Span arrangement; Construction & Building Technology; Engineering